2007
DOI: 10.1111/j.1365-2966.2007.11640.x
|View full text |Cite
|
Sign up to set email alerts
|

The Monitor project: rotation of low-mass stars in the open cluster NGC 2516

Abstract: We report on the results of an i‐band time‐series photometric survey of NGC 2516 using the Cerro Tololo Inter‐American Observatory (CTIO) 4‐m Blanco telescope and 8k Mosaic‐II detector, achieving better than 1 per cent photometric precision per data point over 15 ≲i≲ 19. Candidate cluster members were selected from a V versus V−I colour–magnitude diagram over 16 < V < 26 (covering masses from 0.7 M⊙ down to below the brown dwarf limit), finding 1685 candidates, of which we expect ∼1000 to be real cluster membe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
193
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(206 citation statements)
references
References 76 publications
(131 reference statements)
12
193
1
Order By: Relevance
“…Estimates of the timescale for coreenvelope coupling in solar-type stars range from about 1 Myr for the fastest rotators up to 10−100 Myr (e.g. Keppens et al 1995;Alain 1998) and 0.5 Gyr (Irwin et al 2007) for slowly rotating stars. Models of rotational evolution of solar-type stars with angular momentum transport described as a purely diffusive process show that these coupling time intervals correspond to large diffusion coefficients that would lead to rates of surface Li destruction strongly exceeding the trend observed in the Sun and its twins .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estimates of the timescale for coreenvelope coupling in solar-type stars range from about 1 Myr for the fastest rotators up to 10−100 Myr (e.g. Keppens et al 1995;Alain 1998) and 0.5 Gyr (Irwin et al 2007) for slowly rotating stars. Models of rotational evolution of solar-type stars with angular momentum transport described as a purely diffusive process show that these coupling time intervals correspond to large diffusion coefficients that would lead to rates of surface Li destruction strongly exceeding the trend observed in the Sun and its twins .…”
Section: Discussionmentioning
confidence: 99%
“…Photometric monitoring programs have produced a large number of measurements of this kind in young open clusters (e.g. Prosser et al 1995;Krishnamurthi et al 1998;Irwin et al 2007;Collier Cameron et al 2009;Hartman et al 2009Hartman et al , 2010. Based on these data, Barnes (2003a) found that young stars tend to group into two main sub-populations that lie on narrow sequences in diagrams where the measured rotation periods of the members of a stellar cluster are plotted against their B − V colour indices.…”
Section: Introductionmentioning
confidence: 99%
“…These new observational results provide extremely useful guidance for the modelling of angular momentum evolution of low-mass stars (M * < 1.2 M ) from 1 Myr to 10 Gyr (e.g. Irwin et al 2007;Bouvier 2008;Denissenkov et al 2010;Spada et al 2011;Reiners & Mohanty 2012;Gallet & Bouvier 2013) and offer a unique insight into the physical processes that dictate rotational evolution. To account for the observations, parametric models have to incorporate at least three major processes: the star-disk interaction during the early pre-main sequence (PMS; Matt & Pudritz 2005b;Zanni & Ferreira 2009Ferreira et al 2000;Matt et al 2010), the loss of angular momentum through powerful stellar winds on the early main sequence (MS; Weber & Davis 1967;Kawaler 1988;Matt & Pudritz 2005a;Vidotto et al 2011Vidotto et al , 2014bZanni & Ferreira 2011;Cranmer & Saar 2011;Matt et al 2012a,b;Reiners & Mohanty 2012;Réville et al 2015), and the redistribution of angular momentum in the stellar interior at all phases of evolution (MacGregor & Brenner 1991;Allain 1998;Palacios et al 2003Palacios et al , 2006Charbonnel & Lagarde 2010;Lagarde et al 2011Lagarde et al , 2012Charbonnel et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Observations of rotational periods for young solar-type stars in open clusters suggest that slow rotators develop a high degree of differential rotation between the radiative core and the convective envelope, while solid-body rotation is favoured for fast rotators (Irwin et al 2007;Bouvier 2008;Denissenkov et al 2010;Denissenkov 2010). Models including a detailed treatment of shellular rotation show however that meridional circulation and shear mixing alone do not couple the core and envelope, even in the presence of rapid rotation (Eggenberger et al 2010a).…”
Section: Introductionmentioning
confidence: 99%